Evidence-based management of non-variceal upper GI bleeding - Sung, Joseph J. (Henry Stewart Talks, 2011)
Upper gastrointestinal bleeding is an important medical emergency, The literature has provided many evidence-based management strategies, Early endoscopy within 24 hours should be provided, Injection for active ulcer bleeding should not be used as a monotherapy, Thermal device (heat probe) is comparable to mechanical device (hemoclips), Underlying vessel beneath blood clot should exposed and treated, Pre-endoscopy use of proton pump inhibitor may reduce need for endoscopic therapy, Intravenous proton pump inhibitor is an important adjuvant to endoscopic therapy, Routine second-look endoscopy is not recommended, Surgery is still providing the ultimate hemostasis in selected cases, Support of cardiopulmonary conditions is important to reduce mortality, Anti-platelet agent should be restarted as soon as patient's condition stabilizes